Interregional contact and national identity - Christopher Roth; Manuel Bagues (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Countries across Europe have struggled in recent decades to prevent secessionist movements, win wide support for social safety nets, and tackle problems demanding collective action. This column argues that to accomplish such goals requires a sense of shared, national identity. Exploiting a unique natural experiment – the random assignment of conscripts in Spain to serve outside their home region – it finds that intergroup contact in early adulthood can encourage interregional social cohesion. Governments looking to promote national identity should consider policies, such as mobility in higher education, that bring together people from different regions.
Keywords: 330